Perturbations in polar lipids, starvation survival and reproduction following exposure to unsaturated fatty acids or environmental toxicants in Daphnia magna. (February 2016) - Sengupta, Namrata; Gerard, Patrick D.; Baldwin, William S.
Abstract: Acclimating to toxicant stress is energy expensive. In laboratory toxicology tests dietary conditions are ideal, but not in natural environments where nutrient resources vary in quality and quantity. We compared the effects of additional lipid resources, docosahexaenoic acid (n-3; DHA) or linoleic acid (n-6; LA), or the effects of the toxicants, atrazine or triclosan on post-treatment starvation survival, reproduction, and lipid profiles. Chemical exposure prior to starvation had chemical-specific effects as DHA showed moderately beneficial effects on starvation survival and all of the other chemicals showed adverse effects on either survival or reproduction. Surprisingly, pre-exposure to triclosan inhibits adult maturation and in turn completely blocks reproduction during the starvation phase. The two HR96 activators tested, atrazine and LA adversely reduce post-reproduction survival 70% during starvation and in turn show poor fecundity. DHA and LA show distinctly different lipid profiles as DHA primarily increases the percentage of large (>37 carbon) phosphatidylcholine (PC) species and LA primarily increases the percentage of smaller (<37 carbon) PC species. The toxicants atrazine and triclosan moderately perturb a large number of different phospholipids including several phosphatidylethanolamine species. Some of these polar lipid species may be biomarkers for diets rich in specific fatty acids or toxicant classes. Overall our data demonstrates that toxicants can perturb lipid utilization and storage in daphnids in a chemical specific manner, and different chemicals can produce distinct polar lipid profiles. In summary, biological effects caused by fatty acids and toxicants are associated with changes in the production and use of lipids. Highlights: Chemical exposures alter Daphnia magna's starvation stress responses. Triclosan inhibits adult maturation and blocks reproduction during starvation. DHA supplementation increases starvation survival and does not perturb reproduction. The ratio of phosphatidylcholines to phosphatidylethanolamines was perturbed in all groups. Each chemical exposure induced specific changes in the profiles of polar lipids.